Modeling of Charcot-Marie-Tooth disease in zebrafish - Korzeniowska née Wiweger, Małgorzata; Chabros, Katarzyna; Rzepnikowska, Weronika; Kochański, Andrzej; Kabzińska, Dagmara (Frontiers in Molecular Neuroscience, 2025)
Charcot–Marie–Tooth (CMT) disease is one of the most common inherited neuromuscular disorders, characterized by progressive peripheral nerve degeneration, muscle weakness, and sensory loss. To date, no effective therapy has been developed for CMT. The extreme genetic heterogeneity of CMT, encompassing mutations in more than 50 genes and the involvement of diverse pathological mechanisms, continues to pose significant challenges for disease modeling and therapeutic development. To address these challenges and interrogate specific hypotheses with greater experimental control, researchers have increasingly turned to alternative model organisms that offer genetic tractability and in vivo functional readouts. Zebrafish models have been employed to study hallmark features of CMT, including motor deficits, sensory dysfunction, skeletal abnormalities, and auditory neuropathy. Through the use of forward and reverse genetic screening approaches, as well as transgenic lines, zebrafish have yielded some interesting insights into the functional roles of specific genes implicated in CMT and the effects of pathogenic mutations. Moreover, zebrafish serve as a versatile platform for evaluating potential therapeutic interventions, including pharmacological compounds and gene therapy strategies. This review underscores the value of zebrafish as a robust model for advancing our understanding of CMT pathophysiology. It also addresses the ongoing challenges in genetic diagnosis and highlights the therapeutic potential of this model in guiding future treatments for CMT.